2003
DOI: 10.1038/nature01996
|View full text |Cite
|
Sign up to set email alerts
|

High-performance thin-film transistors using semiconductor nanowires and nanoribbons

Abstract: Thin-film transistors (TFTs) are the fundamental building blocks for the rapidly growing field of macroelectronics. The use of plastic substrates is also increasing in importance owing to their light weight, flexibility, shock resistance and low cost. Current polycrystalline-Si TFT technology is difficult to implement on plastics because of the high process temperatures required. Amorphous-Si and organic semiconductor TFTs, which can be processed at lower temperatures, but are limited by poor carrier mobility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
725
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 905 publications
(736 citation statements)
references
References 22 publications
7
725
0
4
Order By: Relevance
“…Moreover, nanowire/nanotube networks (nanomat/nanobundles) are also possible solutions [46][47][48] . We recently reported transistors consisting of up to 22 ZnO nanowires assembled in parallel and have shown that on-current levels scale with the number of nanowires and with negligible degradation in the subthreshold slope 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nanowire/nanotube networks (nanomat/nanobundles) are also possible solutions [46][47][48] . We recently reported transistors consisting of up to 22 ZnO nanowires assembled in parallel and have shown that on-current levels scale with the number of nanowires and with negligible degradation in the subthreshold slope 49 .…”
Section: Resultsmentioning
confidence: 99%
“…32 High-performance top-gated graphene transistors can have normalized transconductance values 33 as high as 1.27 mS/μm, while carbon nanotubes can reach transconductance of 2.3 mS/μm. 34 We expect that lowering the channel length will reduce the number of scattering centers and increase the oncurrent in MoS 2 -based transistors.…”
mentioning
confidence: 99%
“…for chemical/biological sensing applications and their ability to be solution-processed and assembled from "semiconducting inks" using various alignment techniques, make them potential key building blocks for the manufacturing of chemical and biological sensors, [1][2][3] high performance field-effect transistors (FETs), [4][5][6] optical devices, 7,8 memory elements [9][10][11] and energy harvesting. 12,13 The availability of high quality semiconducting NWs in scalable quantities remains one of the main challenges for NW-based printed electronics.…”
mentioning
confidence: 99%